Pembangunan Sistem Helpdesk Ticketing Berbasis Web Menggunakan Framework Laravel - Ahmad Muhajir; Eko Darmanto (JURPIKAT, 2026)
The Information Systems Institute (LSI) of Muria Kudus University (UMK) plays a crucial role in providing technical support (IT Support) for all work units and academics. In daily operations, communication processes and constraints have been responsively managed through telephone lines and instant messaging platforms (such as WhatsApp and SMS). However, the high volume of requests poses administrative challenges, with reports often leading to bottlenecks in certain individuals, prone to being lost, and the lack of an integrated ticketing system making it difficult for strategic units such as LSI, BAAK, and BAU to concisely compile recapitulation data. To improve this communication flow, "Helpdesk: UMK Campus Complaints System," an integrated web-based helpdesk application, was developed. This system was built using the Laravel 12 framework and, the interface was developed using Tailwind CSS to produce a user-friendly User Interface (UI) and User Experience (UX), supported by MySQL as the basic data management system. The result of this development is a one-stop reporting portal that is able to structure complaint communications into queue tickets. The presence of Helpdesk facilitates the distribution and tracking of technician tasks, as well as providing an accurate historical database for leaders and between work units to spread the quality of information technology services at Muria Kudus University.